A Survey of Age and Sex Differences in Anthropometric Dimension and Motor Performance Due to Strength in Preschool Children - Robabeh Rostami; Gholamhossien Nazemzadegan; Sousan Jabbari (University of Tehran, 2012)
Psychological and educational findings show that preschool years play a very important role in educating and developing children. One of the dimensions of development is motor development. The survey of motor performance with respect to anthropometric characteristic is of utmost importance. Thus, the aim of this study was to survey the relationship between dimensional anthropometric characteristic and motor performance and to determine the difference in motor performance in all preschool children from Shiraz city (157 boys and girls aged between 3 and 6). The method of this research was analytical descriptive. Demographic information form, (AC) recording sheet and motor performance test were used to collect data. One-way ANOVA, Pearson correlation coefficient and t test were used to analyze the data. The results showed significant differences between girls and boys in vertical jump (F=25.47, df=2, P?0.000) and horizontal jump (F=14.15, df=2, P?0.000). 5-year-old subjects were stronger in vertical jump and 4-year-old subjects in horizontal jump. Also, boys were better in vertical jump (t=1.70, df=155, P?0.008) and ball throwing (t=1.98, df=155, P?0.030). In investigation of the relationship between dimensional AC and motor performance, weight and length dimension showed the highest relationship. The results showed the gradual increment of muscular strength parallel with age. Gender difference observed in some variables necessitates more research. It is suggested that other samples and tools be used in anthropometric characteristics.